A new species of Pachyseius Berlese (Acari: Pachylaelapidae) from South Siberia (Russia), with a key to the species known from Asia - Marchenko, Irina I. (Zootaxa, 2015)
Pachyseius anisimovi sp. nov. is described based on specimens from soil and litter in the Altai Mountains and the West and East Sayan Mountains in South Siberia, Russia. A key to ten Pachyseius species known from Asia is provided.